2011
DOI: 10.1007/s12257-011-0215-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential agents for cancer and obesity treatment with herbal medicines from the green garden

Abstract: Many classes of bioactive drug-like molecules derived from traditional herbal plants are becoming attractive as alternative medicines for the treatment of severe chronic diseases such as cancer and obesity. A set of chemically synthesized drugs that is capable of both inhibiting cancer growth and reducing body weight for treatment of obesity have severe side effects including nausea, vomiting, diarrhea as well as producing increased blood pressure and headache, respectively. For decades, drug candidates from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 71 publications
0
22
0
2
Order By: Relevance
“…Although several available antiobesity drugs, including orlistat [4], rimonabant [5], and sibutramine [6], have been approved as a therapeutic strategy to combat obesity, the potential toxicity may limit their overall usefulness [7]. Herbal medicines can be defined as raw or extracted products isolated from plants, and they are widely used for prevention and treatment of many chronic diseases, including obesity, because they have fewer side effects compared with pharmacological drugs [8]. Pericarpium citri reticulatae, also called Chenpi in Chinese, is the dried ripe fruit peel of Citrus reticulata Blanco and its cultivars [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although several available antiobesity drugs, including orlistat [4], rimonabant [5], and sibutramine [6], have been approved as a therapeutic strategy to combat obesity, the potential toxicity may limit their overall usefulness [7]. Herbal medicines can be defined as raw or extracted products isolated from plants, and they are widely used for prevention and treatment of many chronic diseases, including obesity, because they have fewer side effects compared with pharmacological drugs [8]. Pericarpium citri reticulatae, also called Chenpi in Chinese, is the dried ripe fruit peel of Citrus reticulata Blanco and its cultivars [9].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal herbal supplements are being extensively utilized due to their effectiveness in managing many chronic disorders. They are cost-effective, and exert less to no toxic side-effects in comparison with many chemically synthesized drugs [15]. Accordingly, recent preliminary reports suggested that herbs with a long history of use and other natural substances less likely to produce severe toxicity might be effective in reducing appetite and promoting significant weight loss are encouraging [16].…”
Section: Introductionmentioning
confidence: 99%
“…Even European marketing authorizations for phentermine–topiramate and lorcaserin were refused by The European Medicines Agency due to safety concerns . For years, drug candidates from natural herbal products have been considered as potential therapeutic agents because they are generally cost‐effective and exert little‐to‐no toxic side effects in comparison with the synthetic drugs . Several review articles suggested that traditional medicinal herbs with a long history of use along with other natural substances less likely to produce severe toxicity might reduce appetite and promote weight loss .…”
Section: Introductionmentioning
confidence: 99%
“…[22] For years, drug candidates from natural herbal products have been considered as potential therapeutic agents because they are generally cost-effective and exert little-to-no toxic side effects in comparison with the synthetic drugs. [24,25] Several review articles suggested that traditional medicinal herbs with a long history of use along with other natural substances less likely to produce severe toxicity might reduce appetite and promote weight loss. [25,26] Therefore, various extracts and compounds from natural resources are being studied to identify alternative therapeutic options for treating obesity without significant side effects.…”
Section: Introductionmentioning
confidence: 99%